1997
DOI: 10.1080/10473289.1997.10464067
|View full text |Cite
|
Sign up to set email alerts
|

Application of Computational Methods for the Determination of Traffic Emissions

Abstract: A mathematical model, taking into account the interactions between the adsorption, microkinetics, mass transfer, and gas flow patterns in biofilters, was developed to describe the transient behavior of the biofiltration process. Transient responses of biofilters as affected by the compost and by inert particles were estimated separately. In addition, time delay of the microbial growth was also considered. Simulated results were compared with previous experimental data obtained in three laboratoryscale biofilte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Processing with biofiltration involves the utilization of bacteria as a breakdown of pollutant elements that enter the liquid waste; later, these bacteria will be mobilized into the biofilm that has been formed, and the presence of biofilm and bacteria in the media will attract pollutants, which are in charge of breaking down pollutant elements into elements that are safer to release into the environment [12]. Several studies have shown that biofiltration can also be used to reduce pollutants in industrial gas waste and eliminate odor disturbances that may arise from gases containing harmful pollutants [13][14][15][16][17]. This is because biofiltration is known can remove volatile organic compounds [18].…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Processing with biofiltration involves the utilization of bacteria as a breakdown of pollutant elements that enter the liquid waste; later, these bacteria will be mobilized into the biofilm that has been formed, and the presence of biofilm and bacteria in the media will attract pollutants, which are in charge of breaking down pollutant elements into elements that are safer to release into the environment [12]. Several studies have shown that biofiltration can also be used to reduce pollutants in industrial gas waste and eliminate odor disturbances that may arise from gases containing harmful pollutants [13][14][15][16][17]. This is because biofiltration is known can remove volatile organic compounds [18].…”
Section: Review Articlementioning
confidence: 99%
“…However, many bio-filtration designers currently focus only on the absorption properties of biofilters rather than the formation of bacterial colonies, which will later break down pollutant elements into elements that are harmless to the environment [29][30][31][32]. The lack of information about the performance of biofilter reactors on technical and semi-technical scales is an obstacle in the development of this science because most of the previous research was carried out at the laboratory scale [15,17,28,30,33].…”
Section: Review Articlementioning
confidence: 99%